The relative age effect in Austria youth alpine ski racing - Müller, L.; Hildebrandt, C.; Ehn, G.; Müller, E.; Raschner, C. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
A relative age effect (RAE) consists of an over-representation of athletes born early in a selection year (Musch & Grondin, 2001). This effect was recently shown for top elite alpine ski racers (FIS World Cup, FIS Junior World Ski Championships) and the participants of the entrance exams of Austrian ski boarding schools (Müller et al., 2012). However, it is still unknown at which age this effect starts to exist in alpine skiing.